Influences of Pressure and Green Supply Chain Management on Sustainable Performance of Green Manufacturing Industry in Thailand - Mongkhol Yupat; Nuttawut Rojniruttikul (My University, 2024)
Introduction: Green industries play an important role in economic and social development. The market situation is an important factor for the organizations to be developed with regard to technology, regulations of the government, stakeholders, and the competitors, which all affect the revenue of the companies that are faced with the pressure. Thus, the companies implement the Green Supply Chain Management to obtain advantages over their competition. The Green Supply Chain Management increases the competitiveness and resolves the trade dispute issues. The Green Supply Chain Management is a convergence of the elements of environmental management and supply chain management of the organizations that Thai manufacturers cannot avoid. Objective: This study aims to develop the pressure model and green supply chain management that affect the sustainable performance of green industries in Thailand Method: The study uses a Quantitative Research method, and the data was collected using a survey of 250 factory managers as well as analysis with the structural equation model (SEM). Results: The findings reveal that Pressure has a positive direct effect on sustainability performance and Green Supply Chain Management. And, Green Supply Chain Management (GSCM) has a positive influence on sustainability performance. Conclusion: Pressure and Green Supply Chain Management positively impact the Green Manufacturing Industry's sustainability performance. Furthermore, Market Needs, Regulations, Stakeholders, and Competitors have a significant impact on the improvement of the competitiveness of organizations. They also promote social and community responsibility throughout the supply chain, enhancing the competitiveness and sustainability of the Green Manufacturing Industry in Thailand in order to develop sustainable economic and social environments.
Keywords: Manufacturing; Green innovation; Sustainable Supply Chain Management